Relationship of gas exchanges in different phenological phases with coffee productivity in the Cerrado (Research, Society and Development, 2020)
Coffee growing has been expanding in the Brazilian Cerrado. To identify genotypes adapted to the conditions, in 2015, an experiment was implanted with 35 genotypes of Coffea arabica, irrigated, in Ceres, Goias, Brazil, latitude 15°21′00.67′′, longitude: 49°35′56.98′′, Altitude approximately 570 m. The coffee trees showed differences in growth and, in the first harvest, were grouped into low, medium and high productivity. Seeking to understand the divergences in growth and productivity between coffee trees, gas exchange between 9:00 - 10:00 h was evaluated; 12:00 - 13:00 h and 15:00 - 16:00 h, in five phenological phases of the second harvest (fruit formation, fruit filling, maturation, after harvest and vegetative phase), of three coffee trees (Sarchimor MG 8840, Catucaí Amarelo 2SL and IBC - Palma 2) with high, medium and low productivity, respectively, in the first harvest. The genotypes showed the same pattern of productivity in the first and second crop. Gas exchange in coffee trees, with different productive potential, grown in the Cerrado, under irrigation, varied between genotypes and phenological phases. The best results prevailed in the formation and filling phases of the fruits. Variation of the genotypes was observed between the phenological phases. Despite the differences found, gas exchange does not explain the divergences in the growth and production responses of the studied genotypes, indicating the involvement of other factors in the growth and productivity of coffee trees cultivateds in the Cerrado.